An extreme high-performance ultraviolet photovoltaic detector based on a ZnO nanorods/phenanthrene heterojunction. Issue 15 (29th January 2016) - Cheng, Wentao; Tang, Libin; Xiang, Jinzhong; Ji, Rongbin; Zhao, Jun
Abstract : ZnO nanorods/Phen heterojunction based UV photovoltaic detector is fabricated which shows an extremely high performance with a detectivity up to ∼9.0 × 10 13 Jones. Abstract : Ultraviolet (UV) photodetectors are important optoelectronic devices. The development of a high-performance UV detector, however, has been impeded by lack of stable p-type wide gap semiconductors. Herein, an extremely high UV response for a ZnO nanorods/phenanthrene (Phen) photovoltaic detector has been realized, utilizing phenanthrene as a p-type wide gap organic semiconductor; a detectivity ( D *) as high as ∼9.0 × 10 13 cm Hz 1/2 W −1 has been reached, showing significant potential for optoelectronic applications.